Component analysis of cultivated ginseng, cultivated wild ginseng, and natural wild ginseng by structural parts using HPLC method - Young-Ju,Han; Ki-Rok,Kwon; Bae-Chun,Cha; Oh-Man,Kwon (Korean Pharmacopuncture Institute, 2007)
Objectives : The aim of this experiments is to provide an objective differentiation of ginseng, Korean and Chinese cultivated wild ginseng, and natural wild ginseng through components analysis of different parts of ginseng. Methods : Comparative analyses of ginsenoside-, ginsenoside-, and ginsenosides and from the root, stem, and leaves of ginseng, Korean and Chinese cultivated wild ginseng, and natural wild ginseng were conducted using HPLC. Results : 1. For content comparison of leaves, ginseng showed highest content of ginsenoside than other samples. Natural wild ginseng showed relatively high content of ginsenosides and than other samples. 2. For content comparison of the stem, ginseng and 10 years old Chinese cultivated wild ginseng didn't contain ginsenoside . Natural wild ginseng showed higher content of ginsenosides and than other samples. 3. For content comparison of the root, ginsenoside was found only in 5 and 10 years old Korean cultivated wild ginseng. 4. Distribution of contents by the parts of ginseng was similar in ginseng and Chinese cultivated wild ginseng. Conclusions : Above experiment data can be an important indicator for the identification of ginseng, Korean and Chinese cultivated wild ginseng, and natural wild ginseng.